Knee function among elite handball and football players 1-6 years after anterior cruciate ligament injury - Myklebust, G.; Bahr, R.; Nilstad, A.; Steffen, K. (Scandinavian Journal of Medicine & Science in Sports, 2017)
The aim of the study was to describe objective and self-reported knee function for athletes who have returned to elite handball and football play after an ACL injury, comparing these to non-injured players at the same level. A total of 414 handball and 444 football players completed baseline tests from 2007 through 2014, examining lower extremity strength, dynamic balance, knee laxity, and knee function (KOOS questionnaire). Measures were compared between injured and non-injured legs and between injured legs and legs of controls. Eighty (9.3%) of the 858 players reported a previous ACL injury, 1-6 years post-injury (3.5±2.5 years), 49 handball (61.3%) and 31 football players (38.7%). We found no difference in strength or dynamic balance between previously ACL-injured (N=80) and non-injured players legs (N=1556). However, lower quadriceps (6.3%, 95% CI: 3.2-9.2) and hamstrings muscle strength (6.1%, 95% CI: 3.3-8.1) were observed in previously ACL-injured legs compared to the non-injured contralateral side (N=80). ACL-injured knees displayed greater joint laxity than the contralateral knee (N=80, 17%, 95% CI: 8-26) and healthy knees (N=1556, 23%, 95% CI: 14-33). KOOS scores were significantly lower for injured knees compared to knees of non-injured players. ACL-injured players who have successfully returned to elite sport have comparable strength and balance measures as their non-injured teammates. Subjective perception of knee function is strongly affected by injury history, with clinically relevant lower scores for the KOOS subscores Pain, Function, Sport, and Quality Of Life.